Hypoxia decreases the T helper cell-suppressive capacity of synovial fibroblasts by downregulating IDO1-mediated tryptophan metabolism - Kaul, Nathalie-Christin; Mohapatra, Soumya R.; Adam, Isabell; Tucher, Christine; Tretter, Theresa; Opitz, Christiane; Lorenz, Hanns-Martin; Tykocinski, Lars-Oliver (Rheumatology, 2020)
AbstractObjective. The development of RA is linked to local infiltration of immune cells and to changes in the phenotype of synovial fibroblasts. Synovial fibr